2008
DOI: 10.1007/s00417-008-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on antiviral activity of silicone oil in vitro

Abstract: Silicone oil has an antiviral function against HSV-1. The antiviral effect of silicone oil is correlated with concentration of virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Besides this therapeutic use of silicone oil endotamponade, some authors suggest that initially using a prophylactic silicone oil endotamponade during vitrectomy could lead to better overall results in the treatment of retinal necrosis [31]. However, this conclusion is definitely limited by the small sample size due to the rarity of the disease but could be supported by the finding that silicone oil has an antiviral effect in vitro [32]. …”
Section: Redetachment Rates and Other Findings After Oil Removalmentioning
confidence: 70%
See 1 more Smart Citation
“…Besides this therapeutic use of silicone oil endotamponade, some authors suggest that initially using a prophylactic silicone oil endotamponade during vitrectomy could lead to better overall results in the treatment of retinal necrosis [31]. However, this conclusion is definitely limited by the small sample size due to the rarity of the disease but could be supported by the finding that silicone oil has an antiviral effect in vitro [32]. …”
Section: Redetachment Rates and Other Findings After Oil Removalmentioning
confidence: 70%
“…The effect of laser treatment is still controversial, but retinal detachment is seen less frequently after vitrectomy, which could be due to removal of vitreous traction on the weakened retina. Several groups reporting small case series have found high anatomical success rates of up to 100% for vitrectomy with silicone oil endotamponade for retinal detachment secondary to acute retinal necrosis, but only little functional recovery [27,28,29,30,31,32]. Besides this therapeutic use of silicone oil endotamponade, some authors suggest that initially using a prophylactic silicone oil endotamponade during vitrectomy could lead to better overall results in the treatment of retinal necrosis [31].…”
Section: Redetachment Rates and Other Findings After Oil Removalmentioning
confidence: 99%
“…Silicone oil has a longer duration owing to its lower density and higher surface tension than water 77 . Additionally, studies have shown that silicone oil can inhibit the growth of residual pathogenic bacteria in the eye 78,79 …”
Section: Resultsmentioning
confidence: 99%
“…For proving the antimicrobial and antiviral activity of silicone oil, we have performed two experiments, including an experimental study on antimicrobial activity of silicone oil in vitro and experimental study on antiviral activity of silicone oil in vitro (4,5). In the experimental study on antimicrobial activity of silicone oil in vitro, the antiviral activity of silicone oil against herpes simplex virus-1 (HSV-1) in vitro was studied.…”
Section: Experimental Evidence Of Antiviral and Antimicrobial Activitmentioning
confidence: 99%